Comparing the therapeutic potentials of Lactobacillus johnsonii vs. Lactobacillus acidophilus against vulvovaginal candidiasis in female rats: an in vivo study - ElFeky, Dalia Saad; Awad, Alaa Reda; Shamseldeen, Asmaa Mohammed; Mowafy, Hagar Lotfy; Hosny, Sara Adel (Frontiers in Microbiology, 2023)
Background Vulvovaginal candidiasis (VVC) is a highly prevalent illness affecting women globally. Lactobacilli, which make up the majority of healthy vaginal microbiota (VMB), serve as a powerful barrier against infections. Probiotic therapy has been recommended for the treatment or prevention of VVC. Aim of work To compare the in vivo therapeutic effects of Lactobacillus johnsonii (B-2178) vs. Lactobacillus acidophilus (LA-5®) on VVC in a rat model, particularly highlighting the immune response of the host vaginal epithelium. Methods In total, 30 female Sprague-Dawley rats were divided into 5 groups; Group 1: no intervention, Group 2: ovariectomy group, while animals in Groups 3–5 were subjected to ovariectomy and an intravaginal inoculation of Candida albicans (C. albicans) to establish VVC. The animals in Groups 4 and 5 received intravaginal lactobacilli treatment with L. acidophilus (LA-5®) and L. johnsonii (B-2178) strains, respectively, for 7 days. C. albicans load was measured in a vaginal lavage 1, 3, and 7 days after the stoppage of the treatment. Histological, morphometric, and immunohistochemical studies of the vaginal tissues were done. IFN-γ, IL-4, and IL-17 were measured in the vaginal tissue. Results Both L. johnsonii and L. acidophilus significantly reduced C. albicans vaginal load (250 ± 77.46 and 133.33 ± 40.82 CFU/mL) compared to the count before treatment in both groups (4,850 ± 1419.51 and 4966.67 ± 852.45 CFU/mL) even after 7 days of stoppage of lactobacilli treatment. A statistically significant reduction of the pro-inflammatory cytokines IL-17 and IFN-γ was reported in both treated groups compared to the infected untreated group. L. johnsonii has a significant effect on the reduction of hyphae formation of C. albicans as well as the nuclear factor kappa B (NF-κB) immunostaining density of vaginal tissue compared to L. acidophilus. Moreover, treatment with L. johnsonii significantly minimized the epithelium damage triggered by C. albicans infection and restored normal vaginal architecture as evidenced by the histologic and morphometric studies when compared to L. acidophilus. Conclusion Through maintaining an immune tolerant state in the vaginal epithelium and ameliorating the undesirable uncontrolled inflammatory response in the vaginal tissue, L. johnsonii (B-2178) has the potential to be utilized alone or in combination with other lactobacilli species in probiotic clinical trials to treat or prevent VVC.